Identification of Gracilaria spp. in Gunungkidul Regency, Yogyakarta Indonesia Based on DNA Barcoding Target Cytochrome Oxidase Subunit 1 - Feni Susanti; Ratih Ida Adharini; Kurnia Rahmi; Dini Kartikasari; Ganesan Kandasamy (Marine Science Department Diponegoro University, 2022)
Seaweed is one of the most abundant biological resources in Indonesia. The number of species of Gracilaria spp. in Indonesia encourages the need for studies on diversity. This study aims to identify species diversity and phylogeny analysis of Gracilaria spp. found in Gunungkidul Regency, Yogyakarta. The sample collection was taken in February 2020 at Sepanjang and Krakal Beaches and in September 2020 at Siung and Watukodok Beaches, Gunungkidul, Yogyakarta. This research uses the methods of sample preservation, DNA isolation/extraction, DNA amplification, and COI mtDNA gene sequencing. Molecular identification of Gracilaria spp. successfully performed by DNA barcoding method using a commercial kit (Genaeid Genomic DNA Mini Kit (Plant)). Gracilaria spp. successfully amplified with primers GazF1 and GazR1 encoding the mtDNA COI gene at annealing temperature of 44°C; 44.4°C and 44.6°C. Species Gracilaria spp. that found were G. salicornia (from Sepanjang and Krakal Beach), G. edulis (from Siung Beach), G. arcuata (from Watu Kodok Beach) and Gracilaria sp. (from Krakal Beach). The species of the Krakal Beach specimen of Gracilaria sp. is unknown, however it belongs to the genus Gracilaria, so further identification of the sample is needed. G. arcuata (from Watu Kodok Beach) is recognized as a species of G. arcuata, however it is 12.8 percent genetically distant from the source. Genetic diversity on the Sepanjang, Krakal, and Watu Kodok beaches is included in the high diversity category, while Siung Beach does not have diversity. This research found four species of Gracilaria spp. based on molecular identification in Gunungkidul, Yogyakarta.